Taraxacum officinale Leaves Ethanolic Extract as Immunostimulatory Agent For Reducing Side Effect of Doxorubicin in Sprague Dawley Rats - Kasianningsih, Sri; Rivanti, Erlina; Pratama, Ratih Hardika; Pratama, Nanda Resa; Ikawati, Muthi; Meiyanto, Edy (Indonesian Journal of Cancer Chemoprevention, 2011)
Doxorubicin as chemotherapeutic agent causes immunosuppresive. The aimÃÂ  for this study to determine the effect of ethanolic extract of Taraxacum oficinale (ETO) in immunity system of Sprague DawleyÃÂ  rat that inducedÃÂ  by doxorubicin to observe the profile of immunity cells. Sprague Dawley rats were divided into five groups each groups contain five rats : control doxorubicin group, doxorubicin dose 4,67 mg/kgBW+ ETO dose 1000 mg/kgBW, doxorubicin dose 4,67 mg/kgBW+ ETO dose 500 mg/kgBW, control extract group, and without treatment. Then the number of leukocytes, lymphocytes and neutrophils were analyzedÃÂ  by hematology analyzer, whereas CD8+ T lymphocytes by flowcytometry. Results showed groups ofÃÂ  doxorubicin combined with ETO dose 1000 mg/kgBW and 500 mg/kgBW increased the number of leukocytes, lymphocytes, neutrophils,ÃÂ  cytotoxic CD8 + T cellsÃÂ  T cells comparedÃÂ  to control doxorubicin group. These data presents that etanolic extract of Jombang leaves hasÃÂ  immunostimulatory activity and potential as co-chemotherapy agents. Molecullar mechanism underlaying itÃ¢â¬â¢s immune activity need to be explored in detail.